101 puteri dunia Melayu : sejarah dan legenda - Nisriwani Yahaya; Syed Zulflida S. M. Noor; Malaysia . Jabatan Muzium (Kuala Lumpur : Jabatan Muzium dan Antikuiti, 2003)
History and legends of Malay princesses from the 7th to 20th century
Includes bibliographical references (pages 470-478) and index
Keywords: Kings and rulers -- History; Malaysia -- History; Princesses -- Malaysia; Women, Malay -- Biography; Southeast Asia -- Biography